2019
DOI: 10.28940/terra.v37i4.547
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of nutrients during the development of ‘Méndez’ avocado fruit

Abstract: Balanced and timely nutrition is important to ensure the yield and quality of avocado (Persea americana Mill.) fruit. This research was carried out in the cv. Méndez with the objectives of a) to describe the dynamics of fruit growth and the process of dry matter accumulation in mesocarp, b) to quantify the concentration and accumulation of nutrients in the mesocarp (pulp) during fruit development. In a commercial orchard with site-specif ic fertilization, 20 trees were selected and 30 summer flowering inflores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It should be noted that fruit fall in avocados can be accentuated by a single or excessive application of nitrogen fertilizers when the fruits reach 2/3 or more of their size. Excess nitrogen stimulates a vigorous vegetative flow that exacerbates this problem (Salazar-García, 2007;Salazar-García et al, 2019). The results showed that, under our conditions, there was only a significant fruit drop in the avocado cv.…”
Section: Fruit Dropmentioning
confidence: 70%
“…It should be noted that fruit fall in avocados can be accentuated by a single or excessive application of nitrogen fertilizers when the fruits reach 2/3 or more of their size. Excess nitrogen stimulates a vigorous vegetative flow that exacerbates this problem (Salazar-García, 2007;Salazar-García et al, 2019). The results showed that, under our conditions, there was only a significant fruit drop in the avocado cv.…”
Section: Fruit Dropmentioning
confidence: 70%
“…The leaf samples collected during flowering had significantly higher Al, Ca, Fe, Mg and Mn concentrations, and lower foliar Cu and Zn concentrations than those collected during fruit development. Foliar Ca, Fe, Mg and Mn concentrations are lowest during fruit development due to the nutrient demand from developing fruit [55][56][57]. The foliar Cu concentration can be low during flowering due to Cu demand by flowers [55,57].…”
Section: Discussionmentioning
confidence: 99%